Peran guru pendidikan agama islam dalam membentuk karakter religius siswa melalui pembelajaran, keteladanan, dan pembiasaan nilai Islam. - aris_ramud (Advances In Education Journal, 2025)
This study aims to explore the role of Islamic Religious Education (PAI) teachers in shaping students' religious character through learning approaches, role models, and habituation of Islamic values. Using a qualitative method with a case study approach, data were collected through in-depth interviews, observations, and documentation in Islamic-based elementary education units. The results of the study indicate that PAI teachers play an important role in transmitting religious values, both through contextual teaching of teaching materials, daily behavior that reflects Islamic morals, and through routine religious activities that become the school culture. These three approaches interact synergistically in shaping students' religious character which is reflected in honest, disciplined, and responsible attitudes in everyday life. This study recommends the need to strengthen teachers' capacity in integrating religious values ​​into all aspects of educational activities consistently and sustainably.